Perancangan Sistem Pendaftaran Peserta Didik Baru Berbasis Web Menggunakan Metode Prototype atau Skalabilitas - Eko Setia Budi; Yustiyanto (STMIK Budi Darma, 2023)
Technological developments in the current era of globalization are moving very rapidly and the information circulating is more and more complex so that the world of education must be able to keep abreast of technological developments, especially in the field of computer technology, along with current technological developments. The human need for information at this time has become so easily fulfilled with the presence of the internet, which makes it possible to transfer information in just a matter of seconds. An educational institution cannot be separated from the curriculum, whose job is to handle and supervise those related to educational facilities and infrastructure needed by schools to support the smooth teaching and learning process. As for the software development method used is the Prototype method and the programming language used is PHP, HTML, CSS, and JQuery, as well as for the database using MySQL. The expected results in this web-based academic information system at the Widyastuti Jakarta Kindergarten School, are expected to be a solution to overcome the problems faced.